The Case for Social Rights - Mantouvalou, Virginia (2010)
This is part of the book Debating Social Rights (Oxford, Hart Publishing, 2010) where I am making the case for social rights and Professor Conor Gearty (LSE) is making the case against social rights. This paper argues that social and economic rights, defined as rights to the satisfaction of basic needs, are constitutional essentials at domestic level and claims of the highest priority at supranational level. Their inadequate legal protection in national and supranational orders is not justified. Social rights have common foundations with civil and political rights, but have been neglected in law because of Cold War ideologies. The paper explores the role of courts and the role of legislatures in the protection of social rights, and identifies the key challenges in each of these fields. In the full version of the book, there is further analysis of the issues discussed here. There are also additional sections on global justice and on the horizontal application of rights, which are not included in this paper